The Role of NOD-like Receptors in Recognition of Pathogen-associated Molecular Patterns of Infectious Pathogens and in Development of Inflammation. Part 1. NLR family - A.Ye. Abaturov; A.P. Volosovets; Ye.I. Yulish (Zaslavsky O.Yu., 2013)
The characteristic of the family of pattern-recognizing receptors - NLR - is presented in the review.